The Virtue of Educational Leaders - รตนปุตฺโต พระครูสังฆรักษ์บุญใส (Journal of Educational Review Faculty of Education in MCU, 2018)
Organizations of all types need leaders to set and implement the strategic direction of the objectives and goals of their agencies. "Leadership" is a very important factor to the success or failure of the organization. The agency or organization having a leader who has moral, knowledge, ability, experience, expertise, etc. can compete with the others and achieve its goals as well. "Leadership" refers to the process by which any person or persons use their influence or their stimulus to push other person or group of people to do what they want with success of the group or organization as the goal. Leadership is more or less depending on experience and training of each individual. Therefore, to be recognized in leadership, the leaders have to accomplish with moral, virtue, knowledge and ability and work with honest, transparency and in team.